A Study to Adapt “Puppet Interview Scales of Competence in and Enjoyment of Science” to Turkish Culture - Berrin Akman; Erhan Alabay; Mefharet Veziroglu Celik; Pinar Aksoy; Selahattin Gelbal (Journal of Education in Science, Environment and Health)
Children interact with science from the moment of their birth. By means of the scientific experiences they have as a result of this interaction, children acquire numerous skills related to science at the early ages. These scientific skills and children's orientation towards science such as awareness, attitude, proficiency, inquisitiveness, as well as interest and ability in researching, exploring, problem solving are especially enhanced by effective science education in early childhood. A valid and reliable assessment tool is needed to determine whether children's scientific attitude and orientation are at desirable levels. The aim of this study, which was developed in line with this need, is to examine validity and reliability of Puppet Interview Scales of Competence in and Enjoyment of Science (in original version; Samarapungavan, Mantzicopoulos& Patrick, 2008) in the context of Turkish culture. Data was gathered from 1158 children in 15 provinces in various regions of Turkey. KR-20 was computed to be .96 for the first subscale, .90 for the second subscale, .80 for the third subscale and .87 for the forth subscale. As a result of exploratory factor analysis for validity, the scale was gathered with 41 items and in four sub-dimensions in total. The total variability of all the factors was computed to be 49.35%. The confirmatory factor analysis conducted on another sample revealed that error is within an acceptable range (.63) and adaptation statistics is above .80. The CFI and NFI values -the indicators of the goodness-of-fit index- are above .90. Additionally, IFI value is .98 and the SRMR value is lower than .08. These indicate high model-data conformity. As a result of this study, Puppet Interview Scales of Competence in and Enjoyment of Science were found to be a reliable and valid scale for the Turkish society.